2016
DOI: 10.1590/1678-4324-2016150518
|View full text |Cite
|
Sign up to set email alerts
|

Production and Characterization of Bacteriocin Produced by Lactobacillus Viridescence(NICM 2167)

Abstract: The present study focused on the production optimization of bacteriocin by Lactobacillus viridescence NICM 2167 followed by its purification and characterization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…In treatments with incubation temperatures of 30 and 37° C, the average growth of LAB strain Pr 4.3L was not significantly different, but optimal conditions were observed at 37°C. A previous study showed that Lactobacillus viridescence as an optimum bacteriocin producer grows at 37°C [10]. Similarly, other results stated that the best incubation temperature for LAB growth was 37°C [8].…”
Section: Growth Of Lab Strain Pr 43lmentioning
confidence: 79%
See 2 more Smart Citations
“…In treatments with incubation temperatures of 30 and 37° C, the average growth of LAB strain Pr 4.3L was not significantly different, but optimal conditions were observed at 37°C. A previous study showed that Lactobacillus viridescence as an optimum bacteriocin producer grows at 37°C [10]. Similarly, other results stated that the best incubation temperature for LAB growth was 37°C [8].…”
Section: Growth Of Lab Strain Pr 43lmentioning
confidence: 79%
“…In the treatment with pH variations, the highest LAB growth was at pH 7. Furthermore, previous studies showed that the highest growth was also at pH 7 [10]. However, some showed that the best LAB growth was at pH 6.2 [5].…”
Section: Growth Of Lab Strain Pr 43lmentioning
confidence: 96%
See 1 more Smart Citation
“…It may not, however, be suitable for all peptides. For this reason, if the aforementioned method is unsuccessful, alternate options such as chemical solvents, ion exchange, and gel chromatography [ 86 ] could be explored. Ammonium sulphate has previously been used as an effective chemical solvent to precipitate peptides from bacterial cultures without destroying bioactivity [ 87 ].…”
Section: The Isolation Purification and Characterisation Of Bacteriocinsmentioning
confidence: 99%
“…In general, the three isolates demonstrated optimal inhibition activity against the tested bacteria after 24 and 72 h of incubation [37]. Also Kp et al(2016) [38] found protein concentration higher after 48 h of incubation than post 24 and 72 h from incubating. The highest inhibition zone was recorded at pH 6.5 at 35ᴼC after 24h of incubation.…”
Section: Figure (5): Ph Effects On Bacteriocin(s) Productions By Lactobacillus Plantarum H7 Isolatesmentioning
confidence: 99%